THE INTRODUCTION OF THE COMPETENCE-BASED APPROACH IN EDUCATIONAL PROCESS OF TRAINING OF SKIPPERS - Zaytseva, Т.В. (Journal of Information Technologies in Education (ITE), 2015)
The competence-based professional education is the objective phenomenon in education brought to life by social and economic, political and educational and pedagogical factors. One’s competitiveness at the modern job market usually depends on ability to operate new technologies,ability to continuous self-education and fast adaptation to various working conditions. Modern job market imposes the whole layer of new requirements on an employee which are taken into account on inadequate level or aren't taken into account at all in the training syllabus for specialist degree in different subject areas and in maritime education in particular. The main idea of the competence-based approach is that education has to provide not isolated knowledge and skills but to develop students’ ability and readiness for future professional activity in various social and working conditions. The competence-based education, which has been introduced in many countries, is nevertheless a new way of organizing educational process in Ukrainian higher educational institutions. Because maritime education is of international nature, the introduction of the competence-based approach into cadets training program is of immediate importance nowadays.Search for effective forms of the educational process organization, which will allow combining the academic, practical and simulator trainings of specialists in this area, is an integral part of teacher’s work at higher education institution